(untitled) (Journal of Oriental Studies, 2023)
In the history of world literature, the study of the "classics of Oriental literature" has never lost its significance. Alisher Navai was one of the personalities who served humanity on the path of goodness in the history of the literature of the Turkic peoples with their artistic works and moral behavior. One of the topics in the work of Navai, which still requires deep research, is the role of the poet in the formation of Islamic literature among the Turkic elites. In 1481, Nauai translated into Turkish the collection "Arbagin", written in Persian by his teacher Abdirahman Jami. This led to the fact that a new tradition entered the literature of the Turkic peoples. This special phenomenon in the work of Navai was reflected in the "Arbagin" literary tradition of subsequent centuries. The article aims to identify and study the history of the formation of this tradition in Islamic literature and its peculiar manifestations in the works of Navai.